Analisis Pengaruh Faktor-Faktor Penyebab Rework terhadap Kualitas Kinerja Pelaksanaan Proyek Konstruksi Gedung di Kota Denpasar - I Putu Widyarsana; Putu Eny Suhardiyani (Syntax Corporation Indonesia, 2024)
Building construction is always undergoing rework. This can happen due to design errors, the application of work methods that are not in accordance with procedures, or lack of supervision during the construction process. In previous studies, the factors that cause rework include design, management, resources, and the environment. This study analyzes how these factors have an impact on the quality of performance in the implementation of construction projects. Construction projects in Denpasar City are the subject of quantitative and qualitative research. Data was collected through interviews, brainstorming, and questionnaires with experts. With the purposive sampling method, respondents are selected based on predetermined criteria. SmartPLS 3.0 software is used to process the data through the analysis of the average square. The test results show that design, management, resources, and environment affect the quality of construction project implementation performance by 94.40 percent; Outside of the study, this influence was 5.60 percent. With an initial sample value (O) of 0.401, management was the most influential rework factor on the quality of project execution performance, compared to 0.226 for design, 0.261 for resources, and 0.222 for the environment. Therefore, contractors must have the ability to improve management functions during the construction project execution process so that they can reduce the amount of work that has to be done again at a later date.